Mathematical morphology‐based single phase‐to‐ground fault feeder selector for a resonant grounded distribution system. Issue 3 (18th January 2018) - Han, X. L.; Wu, Q. H.; Li, M. S.; Zhang, L. L.
Abstract : In this letter, we present a new single phase‐to‐ground fault feeder selector for a resonant grounded distribution system based on mathematical morphology. A combined morphological filter, which is the average of open–closing and close–opening, is employed to extract the transient component and decaying DC component from the zero‐sequence current signal of each feeder. Afterward, two indices are introduced to measure these components and to distinguish the fault feeder from healthy feeders. Simulation studies are conducted using PSCAD/EMTDC, and the results verify the effectiveness of the proposed method. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.